Case report: Bridging radiation therapy before chimeric antigen receptor T-cell therapy induces sustained remission in patients with relapsed/refractory double-expressor diffuse large B-cell lymphoma with localized compressive symptoms - Yang, Liying; Wu, Mengdi; Yang, Hao; Sun, Xiaorong; Xing, Lijie; Liu, Dan; Xing, Ligang; Yu, Jinming (Frontiers in Immunology, 2024)
Background High-risk double-expressor diffuse large B-cell lymphoma has an inferior prognosis following standard first-line therapy. After failure of second-line therapy, treatment options are limited if accompanied by localized compressive symptoms. Chimeric Antigen Receptor T cell (CAR-T) therapy preceded by bridging radiotherapy may be an effective emerging therapy. Case presentation We report a 66-year-old female patient diagnosed with stage IV double-expressor diffuse large B-cell lymphoma. The patient achieved progressive disease after two cycles of rituximab, cyclophosphamide, liposomal doxorubicin, vincristine, and prednisone and continued to develop cervical lymph node recurrence after second-line therapy. The patient was infused with CAR-T cells after receiving focal bridging radiotherapy and remained in complete response more than 9 months after treatment. In addition, the patients did not experience serious adverse reactions related to radiotherapy as well as CAR-T cell therapy. Conclusions In this article, we describe a patient with double-expressor diffuse large B-cell lymphoma with localized compression symptoms after second-line treatment failure who benefited from CAR-T combined with focal bridging radiotherapy.